Inovasi OPAT SIHAT Sebagai Model Pemberdayaan Anak Sekolah Dasar dalam Pengendalian Vektor DBD Terpadu di Kabupaten Bogor - Nasution, Shinta; Firdaus, Shofiyah Jannatul; Widyatami, Anindita (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
Dengue fever (DHF) is a health problem in Indonesia and is characterized by the highest case of death in children. Therefore, strengthening student flick monitors (Sismantik) with the innovation OPAT SIHAT (Optimize Integrated Flick Monitoring with Sismantik Hebat) which combines four forms of innovation (4K) namely Comic Kotak Petik (Flick Monitoring Detective Group), DHF awareness calendar, flick monitoring card, and local wisdom as a medium for health education is the answer in increasing the effectiveness of integrated DHF vector control. This study aims to develop effective innovations in integrated dengue vector control in elementary school students; by reviewing knowledge and attitudes towards integrated dengue vector control before and after the OPAT SIHAT innovation intervention. The subjects were fifth and sixth grade students at SDN Cibedug 01 (rural) and SDN Kaum Pandak 02 (urban). The sample size was 179 respondents divided into 2 treatment groups and a control group for each location. The type of research used is a true experiment with a 2 x 1 factorial design and using a pre-test post-test control group design. OPAT SIHAT innovation (X1) as an independent variable with two interventions (Indonesian and Sundanese versions), while the dependent variables are knowledge (Y1) and attitude (Y2). The results showed that there were significant differences before and after the intervention of the Indonesian version of the OPAT SIHAT innovation on both variables in both locations (p-value <0.05), while the Sundanese version of the OPAT SIHAT innovation showed significant differences on both variables only in rural areas (p-value <0.05). Thus, the implementation of the Indonesian version of the OPAT SIHAT innovation needs to be expanded to schools in both rural and urban areas through the involvement of Sismantik.